Studi Fenomenologi Makna Hidup Pada Pekerja Seks Komersial: Phenomenological Study of the Meaning of Life in Commercial Sex Workers - Muhammad Arifin; Ramon Ananda Paryontri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Meaning in life is a central construct in existential psychology and is closely related to psychological well-being, particularly among marginalized populations. Specific Background: Commercial sex workers frequently encounter stigma, social exclusion, and psychological distress that shape their personal identity and life orientation. Knowledge Gap: Previous studies have examined self-concept, social stigma, and mental health among commercial sex workers, yet limited research explores how they construct and internalize meaning in life through a logotherapy framework. Aims: This study aims to describe the process of meaning construction among commercial sex workers using a qualitative phenomenological approach grounded in Viktor Frankl’s logotherapy. Results: Findings indicate that participants derive meaning from personal values, responsibility toward family, spiritual reflection, and adaptive attitudes toward suffering, demonstrating freedom of will and the search for purpose despite adverse conditions. Novelty: This study provides an in-depth phenomenological account of meaning construction among commercial sex workers within a logotherapy lens in the Indonesian context. Implications: The findings contribute to existential psychology literature and offer practical insights for counseling interventions and psychosocial rehabilitation programs targeting vulnerable women. Keywords: Meaning In Life, Logotherapy, Commercial Sex Workers, Phenomenology, Existential Psychology Key Findings Highlights: Participants articulate life purpose through family responsibility and spiritual values. Adaptive attitudes toward suffering reflect existential freedom of choice. Phenomenological analysis reveals personal narratives as core sources of life orientation.